Technological map of the lesson in the Russian language - Parii T. V., Kozlova T. V. (Scientific and Educational Areas Under Modern Challenges, 2021)
This article describes the content of the technological map of the Russian language lesson in the 4th grade under the program "School of Russia", taking into account the use of predicted results. The materials of the article may be useful for specialists in the field of pedagogy
Keywords: имя существительное; антонимы; имя прилагательное; adjective; части речи; Personal pronouns; Antonyms; repeated words; parts of speech; noun; Numeral; Main members; личные местоимения; повторяющиеся слова; имя числительное; главные члены